EFFECT OF PROJECT BASED LEARNING MODEL OF CREATIVE THINKING SKILLS IN FLUID DYNAMIC IN SMA - Zaskya Laksmita Utami; Nurdin Bukit; Mariati P Simanjuntak; Motlan Motlan (Jurnal Pendidikan Fisika, 2019)
This study aims to: (1) determine the effect of students' creative thinking skills using the project based learning model. (2) determine the effect of students' creative thinking skills using conventional models. This research is a quasi-experimental type of research. The design in this study used two group pretest-posttest designs. The population of this research is all students of class XI semester 1 of SMA Negeri 9 Medan T.A. 2019/2020 there were 6 classes (192). The sample of this study consisted of two classes, namely class X IPA 1 (experimental class) and class X IPA 3 (control class) taken by cluster random sampling. The number of samples was 72 students. The research instrument was in the form of a project-based creative thinking skills test in the form of an essay test in accordance with aspects of creative thinking skills according to Karen S. Meador. The validity of the test is carried out with content validity, using 2 expert lecturers. Analysis of the data used is the t-test. The results of this study are the influence of project based learning model learning on students 'creative thinking skills and improvement of students' creative thinking skills in its aspect in the medium category.